First Detection and Thermal Characterization of Terminator CO2 Ice Clouds With ExoMars/NOMAD. Issue 22 (18th November 2021) - Liuzzi, Giuliano; Villanueva, Geronimo L.; Trompet, Loïc; Crismani, Matteo M. J.; Piccialli, Arianna; Aoki, Shohei; Lopez‐Valverde, Miguel Angel; Stolzenbach, Aurélien; Daerden, Frank; Neary, Lori; Smith, Michael D.; Patel, Manish R.; et al.
Abstract: We present observations of terminator CO2 ice clouds events in three groups: Equatorial dawn, Equatorial dusk (both between 20°S and 20°N) and Southern midlatitudes at dawn (45°S and 55°S east of Hellas Basin) with ESA ExoMars Trace Gas Orbiter's Nadir and Occultation for MArs Discovery instrument. CO2 ice abundance is retrieved simultaneously with water ice, dust, and particle sizes, and rotational temperature and CO2 column profiles in 16 of 26 cases. Small particles (<0.5 μm) prevail at dusk, while water ice likely provides most source nuclei at dawn. Clouds east of Hellas are found to be dominantly nucleated on surface‐lifted dust. CO2 ice is sometimes detected in unsaturated air together with dust nuclei at dawn, suggesting ongoing sublimation. Depending on latitude and local time, the interplay between particle precipitation and the lifetime of temperature minima (i.e., cold pockets) determines CO2 ice properties. Plain Language Summary: The upper atmosphere of Mars is characterized by the seasonal presence of CO2 ice clouds. Their properties have been long studied, as well as their formation mechanisms in relation to the thermal structure of the atmosphere and its variability. In this study, we present the first observations of these clouds at the terminator (dawn and dusk) by the NOMAD spectrometer onboard the Exomars Trace Gas Orbiter. CO2 ice is detected simultaneously with dust, water ice and the temperature profile. Our results agree with previous findings in terms of how clouds are spatially distributed and their temporal occurrence. However, we also explore the sources of condensation nuclei for CO2 ice particles, showing that water ice is a possible source at dawn near the Equator. We also identify surface‐lifted dust below the CO2 ice clouds observed east of Hellas Basin, suggesting that, at that location, dust could provide nuclei for CO2 ice. CO2 ice is also sometimes detected at temperatures higher than the CO2 freezing point, suggesting ongoing sublimation. In this work we explore for the first time the composition of CO2 ice clouds, which is critical to advance our understanding of how CO2 ice clouds form in the mesosphere at Mars. Key Points: Twenty Six mesospheric CO2 ice clouds were detected with NOMAD SO in Mars Year 35, simultaneously with water ice, dust, and CO2 saturation ratios Equatorial CO2 clouds are observed at 50–80 km altitude at dusk, and 40–60 km at dawn, when water ice likely provides condensation nuclei Six CO2 ice clouds are found east of Hellas basin; their formation is likely sourced by surface‐lifted dust at 40–65 km